Influence of Social Culture Change on PHBS in Tenga Health Center, South Minahasa Community - Lodewyk NN Poluan; Arlin Adam; Andi Alim (Lembaga Pengembangan Kinerja Dosen, 2025)
Socio-cultural transformations brought about by globalization have had a profound impact on various aspects of human life, including public health behavior, where Clean and Healthy Living Behavior (PHBS) serves as a crucial indicator in promotive and preventive health efforts. The working area of the Tenga Community Health Center provides a unique context for examining how these socio-cultural changes affect community health practices. This study aimed to analyze the influence of socio-cultural changes on PHBS within this community. Employing a quantitative approach with a cross-sectional design, the research involved 100 respondents selected through purposive sampling, using a questionnaire that was previously validated and tested for reliability. Data analysis utilized the Chi-Square test and simple logistic regression to assess relationships between socio-cultural variables and PHBS practices. Results indicated that new cultural values (p = 0.013), the role of social media (p = 0.004), and shifts in patterns of social interaction (p = 0.031) significantly influenced PHBS practices, whereas traditional customs (p = 0.076) were not found to have a meaningful effect. These findings underscore that socio-cultural changes substantially shape clean and healthy living behaviors in the community. The study highlights the importance of developing health promotion strategies that are not only scientifically sound but also culturally adaptive, taking into account both emerging global influences and the evolving dynamics of local society. By aligning health promotion efforts with socio-cultural realities, policymakers and health workers can foster more effective interventions to strengthen public awareness and adherence to PHBS. Ultimately, the research suggests that a culturally responsive and context-sensitive approach is essential in sustaining improvements in community health behavior amidst the rapid social and cultural transformations driven by globalization.